Severe DCM phenotype of patient harboring RBM20 mutation S635A can be modeled by patient-specific induced pluripotent stem cell-derived cardiomyocytes - Streckfuss-Bömeke, Katrin; Haas, Jan; Meder, Benjamin (Journal of molecular and cellular cardiology, 2017)
The ability to generate patient-specific induced pluripotent stem cells (iPSCs) provides a unique opportunity for modeling heart disease in vitro. In this study, we generated iPSCs from a patient with dilated cardiomyopathy (DCM) caused by a missense mutation S635A in RNA-binding motif protein 20 (RBM20) and investigated the functionality and cell biology of cardiomyocytes (CMs) derived from patient-specific iPSCs (RBM20-iPSCs). The RBM20-iPSC-CMs showed abnormal distribution of sarcomeric α-actinin and defective calcium handling compared to control-iPSC-CMs, suggesting disorganized myofilament structure and altered calcium machinery in CMs of the RBM20 patient. Engineered heart muscles (EHMs) from RBM20-iPSC-CMs showed that not only active force generation was impaired in RBM20-EHMs but also passive stress of the tissue was decreased, suggesting a higher visco-elasticity of RBM20-EHMs. Furthermore, we observed a reduced titin (TTN) N2B-isoform expression in RBM20-iPSC-CMs by demonstrating a reduction of exon skipping in the PEVK region of TTN and an inhibition of TTN isoform switch. In contrast, in control-iPSC-CMs both TTN isoforms N2B and N2BA were expressed, indicating that the TTN isoform switch occurs already during early cardiogenesis. Using next generation RNA sequencing, we mapped transcriptome and splicing target profiles of RBM20-iPSC-CMs and identified different cardiac gene networks in response to the analyzed RBM20 mutation in cardiac-specific processes. These findings shed the first light on molecular mechanisms of RBM20-dependent pathological cardiac remodeling leading to DCM. Our data demonstrate that iPSC-CMs coupled with EHMs provide a powerful tool for evaluating disease-relevant functional defects and for a deeper mechanistic understanding of alternative splicing-related cardiac diseases.